Characteristics and Outcomes of COVID-19 in Patients on Left Ventricular Assist Device Support. (5th April 2021) - Birati, Edo Y.; Najjar, Samer S.; Tedford, Ryan J.; Houston, Brian A.; Shore, Supriya; Vorovich, Esther; Atluri, Pavan; Urgo, Kimberly; Molina, Maria; Chambers, Susan; Escobar, Nicole; Hsich, Eileen; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: The coronavirus disease 2019 (COVID-19) pandemic continues to afflict millions of people worldwide. Patients with end-stage heart failure and left ventricular assist devices (LVADs) may be at risk for severe COVID-19 given a high prevalence of complex comorbidities and functional impaired immunity. The objective of this study is to describe the clinical characteristics and outcomes of COVID-19 in patients with end-stage heart failure and durable LVADs. Methods: The Trans-CoV-VAD registry is a multi-center registry of LVAD and cardiac transplant patients in the United States with confirmed COVID-19. Patient characteristics, exposure history, presentation, laboratory data, course, and clinical outcomes were collected by participating institutions and reviewed by a central data repository. This report represents the participation of the first 9 centers to report LVAD data into the registry. Results: A total of 40 patients were included in this cohort. The median age was 56 years (interquartile range, 46–68), 14 (35%) were women, and 21 (52%) were Black. Among the most common presenting symptoms were cough (41%), fever, and fatigue (both 38%). A total of 18% were asymptomatic at diagnosis. Only 43% of the patients reported either subjective or measured fever during the entire course of illness. Over half (60%) required hospitalization, and 8 patients (20%) died, often after lengthy hospitalizations. Conclusions: We present the largest case series of LVAD patients with COVID-19 to date. Understanding these characteristics is essential in an effort to improve the outcome of this complex patient population.